Toe-to-Heel Air Injection In-situ Combustion Process: Case study from the Azraq Basin, Jordan (Rudarsko-geološko-naftni zbornik, 2020)
The exploration and drilling operations for oil in the Wadi Rajil region of the Azraq Basin in northeast Jordan confirmed the existence of quantities of asphalt and heavy oil in several formations of limestone and dolomite within layers of sandstone. The estimated area was 1200 km2 (120000 hectare) and possibly contained 800 million m3 (five billion barrels) of original oil. The aim of this study is to obtain in-situ combustion and to suggest the application of the drilling of two wells by an in-situ combustion process called Toe-to-Heel Air Injection In-situ Combustion in the Wadi Rajil-Hamzeh field. This approach proposes a pilot project of drilling two wells. One vertical injection well in the upper production zone and another horizontal production well at the bottom of the reservoir. Through this technique, the productivity will increase, the viscosity of the oil will decrease, and consequently the sweep efficiency will be higher. This pilot project’s potential production reaches 212.94 m3/d of oil. The total time for the project to be completed is around 450 days. The efficiency of recovery in this study reached around 65 to 69%. This result can lead to the possible expansion of the approach applied in this project throughout the Wadi Rajil-Hamzeh region.